Mortality Review in a Maxillofacial Center in Northern Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:Mortality pattern is an essential component in health delivery globally. It is an important medical appraisal that should be made regularly. Mortality in maxillofacial patients often results from co-morbidity from others diseases as seen in Ludwig’s angina and advanced stage malignancies.Aim:To document the causes of maxillofacial mortalities during a 12-year period.Materials and Methods:An analysis of all cases of death recorded in the Department of Oral and Maxillofacial Surgery of a Nigerian tertiary health Centre from January 2006 to December 2018.Results:A total of 3255 oral and maxillofacial patients were seen during 12-year period. About 65 deaths were recorded accounting for 2.0% of all cases of which 69.2% were males, whereas 30.8% females. The age group most affected was 30 to 39 with 23.1% closely followed by 20 to 29 with 21.5%.Conclusion:Cervicofacial infection was the commonest causes of mortality in oral and maxillofacial surgery in our environment.